Guidance for reporting intervention development studies in health research (GUIDED): an evidence-based consensus study. Issue 4 (8th April 2020) - Duncan, Edward; O'Cathain, Alicia; Rousseau, Nikki; Croot, Liz; Sworn, Katie; Turner, Katrina M; Yardley, Lucy; Hoddinott, Pat
Abstract : Objective: To improve the quality and consistency of intervention development reporting in health research. Design: This was a consensus exercise consisting of two simultaneous and identical three-round e-Delphi studies (one with experts in intervention development and one with wider stakeholders including funders, journal editors and public involvement members), followed by a consensus workshop. Delphi items were systematically derived from two preceding systematic reviews and a qualitative interview study. Participants: Intervention developers (n=26) and wider stakeholders (n=18) from the UK, North America and Europe participated in separate e-Delphi studies. Intervention developers (n=13) and wider stakeholders (n=13) participated in a 1-day consensus workshop. Results: e-Delphi participants achieved consensus on 15 reporting items. Following feedback from the consensus meeting, the final inclusion and wording of 14 items with description and explanations for each item were agreed. Items focus on context, purpose, target population, approaches, evidence, theory, guiding principles, stakeholder contribution, changes in content or format during the development process, required changes for subgroups, continuing uncertainties, and open access publication. They form the GUIDED (GUIDance for the rEporting of intervention Development) checklist, which contains a description and explanation of each item, alongside examples of good reporting. Conclusions: Consensus-based reporting guidance for intervention development in health research is now available for publishers and researchers to use. GUIDED has the potential to lead to greater transparency, and enhance quality and improve learning about intervention development research and practice.